Traduction et analyses de discours: typologie croisée - Gambier, Yves (Studia Romanica Posnaniensia, 2007)
The article is focussed on tracing all the relations which have existed between science on language and the study of translation. The author makes an attempt at showing in what way the reflection on the theory of discourse may influence translation and, in consequence, on the way translators are instructed.